Advance in the risk genes related to lupus nephritis - Wang, Xiaoyu; Huang, Jiayan; Zhou, Zhifeng; Chen, Qinkai; Lv, Jinlei (American Journal of Translational Medicine, 2021)
Lupus nephritis (LN) is a common and serious complication of systemic lupus erythematosus (SLE). LN is difficult to cure, and current treatment is mainly focused on symptom control. The progress of LN is not completely synchronized with SLE, suggesting that LN might have some special risk genes. Therefore, identifying the risk genes related to LN progression in SLE patients would help clarify its pathogenesis. Moreover, regulating special risk genes and their products might become a new direction for treating LN. In this review, we report the progress of research on the risk genes of LN and their single nucleotide polymorphisms (SNPs) with the aim of supporting the further treatment of LN. [Am J Transl Med 2021. 5 (2): 51-62].